Learning from the Italian experience during COVID-19 pandemic waves: be prepared and mind some crucial aspects. - Deana, Cristian; Rovida, Serena; Orso, Daniele; Bove, Tiziana; Bassi, Flavio; De Monte, Amato; Vetrugno, Luigi (Acta Biomedica Atenei Parmensis, 2021)
COVID-19 pandemic has rapidly spread worldwide causing a serious challenge to the global medical community. Italy was struck hard during the first wave earlier this year and several weaknesses as well as general unpreparedness of the national healthcare system were acknowledged. Learning essential lessons from the past, we realized how implementing contingency response measures, human resources and social dynamics could have changed the outcome if promptly adopted.This review translates the previous experience into strategic actions that has to be considered when developing appropriate national and regional operational plans to respond to a pandemic.